1985
DOI: 10.1002/oms.1210200408
|View full text |Cite
|
Sign up to set email alerts
|

In‐beam ionization by alkali ion attachment applying a two‐filament ion source

Abstract: A simple ion source was constructed for in-beam ionization by alkali ion attachment. A wire probe covered with sample was placed near an alkali ion emitter prepared from a mixture of silica gel and alkali halides. The ionization of various thermally labile compounds and of mixtures was investigated. Na" proved to be the most suitable alkali ion for cationization. For monosaccharides experiments revealed the elimination of water upon ionization by Li+ attachment. The experimental set-up was also examined for me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Ions, such as Na + , leave the sur face and combine in the gas phase with desorbed neu tral molecules via ion-dipole interactions [9,14], Several interesting studies have also been done on IR and thermal desorption of neutrals using postionization techniques. Allison et al [15] and Röllgen et al [16] showed that the emitted neutrals could be ionized in the gas phase by using an intersecting Reprint requests to Dr. J. Grotemeyer, Institut für Physi kalische und Theoretische Chemie, Technische Universität München, Lichtenbergstraße 4, D-8046 Garching, BRD.…”
Section: Introductionmentioning
confidence: 99%
“…Ions, such as Na + , leave the sur face and combine in the gas phase with desorbed neu tral molecules via ion-dipole interactions [9,14], Several interesting studies have also been done on IR and thermal desorption of neutrals using postionization techniques. Allison et al [15] and Röllgen et al [16] showed that the emitted neutrals could be ionized in the gas phase by using an intersecting Reprint requests to Dr. J. Grotemeyer, Institut für Physi kalische und Theoretische Chemie, Technische Universität München, Lichtenbergstraße 4, D-8046 Garching, BRD.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of advantages in using potassium ions here although we do not suggest that it is the optimum cation that can be used for such work (17). Allison and Ridge (25) have shown the ability of an alkali ion to induce fragmentation following complexation decreases when going down the column in the periodic table.…”
Section: Resultsmentioning
confidence: 94%
“…Recently they have reported a technique using a two-filament design (17). In a specially constructed ion source, two filaments are in close proximity, mounted on a common "push rod".…”
mentioning
confidence: 99%
“…All mass spectrometric analysis were performed on an unmodified HP5985 GC/MS/DS quadrupole mass spectrometer (Hewlett-Packard, Avondale, PA) with a mass range of 10-1000 Da equipped with a modified direct insertion probe, similar to that reported previously by Rollgen and co-workers [11] and by Kassel and Allison et a1. [12].…”
Section: Methodsmentioning
confidence: 99%